What Constrains Indian Manufacturing? - Poonam Gupta; Rana Hasan; Utsav Kumar (Indian Council for Research on International Economic Relations (ICRIER), 2008)
India has undertaken extensive reforms in its manufacturing sector in the last two decades. However, an acceleration of growth in manufacturing, and a concomitant increase in employment, has eluded India. What might be holding the sector back? Using Annual Survey of Industries data at the three-digit level and difference in estimates this paper finds that the post-reform performance of the manufacturing sector is heterogeneous across industries. In particular, industries dependent on infrastructure or external finance, and labour-intensive industries have not been able to reap the maximum benefits of reforms. The results point to the importance of infrastructure development and financial sector development for the manufacturing sector's growth to accelerate further. They also emphasize the need to clearly identify and address the factors inhibiting the growth of labour-intensive industries.
Keywords: G1; H5; L5; L6; O2; 330; De-licensing; external finance dependence; infrastructure intensity; labour intensity; manufacturing; reforms; Industrie; Infrastruktur; Finanzsektor; Arbeitsintensität; Indien